1973
DOI: 10.1002/bjs.1800601117
|View full text |Cite
|
Sign up to set email alerts
|

Primary retroperitoneal hydatid cyst

Abstract: A case of a primary retroperitoneal hydatid cyst in an Indian adult which was treated by marsupialization is described. Attention is drawn to the rarity of the lesion, the probable mode of spread, and the difficulties encountered in its diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Primary retroperitoneal hydatid cyst without other organ involvement was first reported by Lockhart J and Sapinza VC in 1958 12. In 1973 Mukherjee et al 13 reported nine cases, two had died due to anaphylactic reaction resulting from spillage during excision or biopsy done with the misdiagnosis of a retroperitoneal tumour. Preoperative diagnosis of retroperitoneal hydatid disease is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Primary retroperitoneal hydatid cyst without other organ involvement was first reported by Lockhart J and Sapinza VC in 1958 12. In 1973 Mukherjee et al 13 reported nine cases, two had died due to anaphylactic reaction resulting from spillage during excision or biopsy done with the misdiagnosis of a retroperitoneal tumour. Preoperative diagnosis of retroperitoneal hydatid disease is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Primary retroperitoneal hydatid cysts without other organ involvement was first reported by Lockhart and Sapinza in 1958 and are rare entities. [2][3][4]6 Various modes of spread have been suggested to explain the escape of liver and lung involvement-via lymphatics 7 or via veno-venous shunts within the liver. 7,8 Airborne transmission and direct implantation of the embryo in the bronchial mucosa is also considered as one of the modes of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The most common complaint is abdominal pain; however, the clinical features may vary according to the location of the cyst in the retroperitoneum. Described here is one such report.…”
Section: Introductionmentioning
confidence: 99%
“…3 Other rare sites include the omentum, ovaries, parametrium, pelvis, 4,5 thyroid, orbit or retroperitoneum. 6 In man, infection is usually acquired in childhood. The symptoms present several years after exposure and it may take five to 20 years before a diagnosis is made.…”
Section: Discussionmentioning
confidence: 99%